2012
DOI: 10.1136/thoraxjnl-2011-200623
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, acute mountain sickness and altitude acclimatisation: a cohort study

Abstract: RationaleThe relationship between cigarette smoking and acute mountain sickness (AMS) is not clear. Objective To assess AMS risk and altitude acclimatisation in relation to smoking. Methods 200 healthy non-smokers and 182 cigarette smokers were recruited from Han lowland workers. These were men without prior altitude exposure, matched for age, health status and occupation, who were transported to an altitude of 4525 masl. Measurements AMS, smoking habits, arterial saturation (SpO 2 ), haemoglobin (Hb), lung fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 32 publications
5
41
0
2
Order By: Relevance
“…Our SaO 2 results are consistent with those of Wu et al7 but contrary to those of Chen et al26 The ascent rate may have accounted for this discrepancy.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our SaO 2 results are consistent with those of Wu et al7 but contrary to those of Chen et al26 The ascent rate may have accounted for this discrepancy.…”
Section: Discussionsupporting
confidence: 75%
“…At high altitudes, the sleep quality of the subjects cannot be adequately assessed by the Lake Louise diagnostic criteria for AMS alone. Among the Lake Louise diagnostic criteria for AMS, subjective insomnia is the second most7 or even the most8 common symptom. However, there are only a few studies on the effects of high-altitude exposure on sleep, all of which used small sample sizes and polysomnography 911.…”
Section: Introductionmentioning
confidence: 99%
“…Schneider (2002) [4] used the Environmental Symptom Questionnaire (ESQ) to diagnose AMS using an ESQ cut-off value of 0.70, which corresponded to a Lake Louise Score (LLS) of 4. Wu (2012) [17] did not provide original data regarding age, gender or BMI. MacInnis (2013) [26] did not provide clear data regarding age or BMI.…”
Section: Resultsmentioning
confidence: 99%
“…Schneider (2002) [4] provided only data regarding the total population of subjects. In addition, we analyzed how the studies defined smoking and found that only one article (Wu (2012) [17]) provided the following clear definition of smoking: “A smoker was someone who smoked 10 or more cigarettes/day for >6 months” …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation